Two Central Obstacles to Russian Academic Excellence - Altbach, Philip (International Higher Education, 2016)
Russian higher education must solve several key problems if world-class status is to be achieved. These include including the academies of science, where most research is done, into the universities, and linking many of the independent medical universities with the mainstream universities.